Experimental and numerical study on damage mode of RC slabs under combined blast and fragment loading. (August 2020) - Li, Ying; Chen, Zhaoyue; Ren, Xianben; Tao, Ran; Gao, Ruxin; Fang, Daining
Highlights: Blast tests were conducted to study the combined loading effects and failure characteristics of two-way RC slabs. Numerical simulation based on FEM-SPH (finite elements-smoothed particle hydrodynamics) method is in good agreement with experiments. The effect of the standoff distances on the damage of the RC slabs is discussed, and analytical expressions are derived. Abstract: This paper aims at investigation of failure characteristic of RC slabs under combined blast and fragment loading. With experimental device designed, blast tests were conducted to study the combined loading effects and failure characteristics of two-way RC slabs. Numerical studies based on FEM-SPH (finite elements-smoothed particle hydrodynamics) method were carried out and good agreement was obtained between numerical simulation and the testing results. The validated numerical model is then used to carry out parametric studies on damage classification. It is demonstrated that there was spall damage, penetration, crack and fragment in concrete slabs under combined loading. Besides, both explosive mass and standoff distance have profound effects on RC slab damage.